Determination of numerical indicators of collection for prevention and treatment of diseases of the musculoskole system - Oproshanska , Tetiana; Khvorost , Olha; Skrebtsova , Kateryna (Annals of Mechnikov’s Institute, 2024)
Diseases of musculoskeletal system are some of the most common in the world which are leading to partial or complete limitation of the patient’s mobility. Treatment of such diseases requires comprehensive and long-term therapy which includes nonsteroidal anti-inflammatory drugs, glucocorticosteroids, analgesics and muscle relaxants are used in therapy to reduce pain. But these drugs have strong side effects with prolonged use. In this aspect, an alternative to synthetic drugs are phytopreparations which have anti-inflammatory, analgesic, antimicrobial, antioxidant, diuretic effects and normalize metabolism. Taking into account the above mentioned and based on the results of our previous studies of plant raw materials, we developed the composition of the original collection “Opornofit” for the prevention and treatment of diseases of the musculoskeletal system with anti-inflammatory and membrane-stabilizing effects. The aim of the work is to determine the following numerical indicators of some series of collection “Opornofit”: loss on drying, total ash, quantitative content of total polyphenols, total hydroxycinnamic acids, total organic acids, and mineral composition. To establish the lower and upper limits of numerical indicators and elements, the study was conducted on 3 series of collections. Plant raw materials were harvested in the summer and autumn of 2022 in Kharkiv region and Vinnytsia region. Loss on drying, quantitative content of total polyphenols, total hydroxycinnamic acids and total organic acids were determined according to monographs of State Pharmacopoeia of Ukraine. Total ash was determined according to monographs of Europian Pharmacopoea 11th edition. Elemental analysis was carried out using the atomic emission spectrographic method with photographic registration on the DFS-8 device. The loss on drying is not more than 12.5 % and the total ash is not more than 7.0 %. The quantitative content of total organic acids in terms of malic acid was not less than 2.2±0.11 %, the total hydroxycinnamic acids in terms of chlorogenic acid was not less than 1.5±0.05 %, the total polyphenols in terms of pyrogallol was not less than 4.4±0.17 %. The elemental composition of the 3 series of collection was the same and represented by at least 19 mineral compounds. In the 3 collection series, the following pattern of macroelements content is observed: K>Ca>Mg. Depending on the collection series, the quantitative content of macroelements K, Ca and Mg and the microelement P fluctuates by 1.3 times. The content of the microelement Si is less variable in the 3 series of collection and fluctuates by 1.1 times. The fluctuation of the content of Fe is 1.4 times, Al – 1.5 times, Mn – 1.8 times and Cu – 1.3 times. The content of the macroelement Na and the microelement Zn is comparable. The quantitative content of elements such as Pb, Mo, Ni, Co <0.03 and Cd, As, Hg <0.01. The content of heavy metals is within permissible limits. Conclusions. For the first time, a number of numerical indicators of the series of the original collection “Opornofit” were determined with the establishment, respectively, of the lower (content of total organic acids, total hydroxycinnamic acids and total polyphenols) and upper (loss on drying and total ash) limits of values. The mineral composition of 3 series of collection was also established. These data will be used in the development of the relevant sections of the project of methods for quality control of the collection “Opornofit”. Keywords: collection, numerical indicators, elemental composition